2022
DOI: 10.3390/ijerph19159190
|View full text |Cite
|
Sign up to set email alerts
|

Simulation on the Evolution Trend of the Urban Sprawl Spatial Pattern in the Upper Reaches of the Yangtze River, China

Abstract: Urban sprawl has become the main pattern of spatial expansion in many large cities in China, and its ecological and environmental effects profoundly impact Chinese urban development. In this paper, nighttime light data and statistical yearbook data are adopted as basic data sources to simulate the evolution trend of the urban sprawl in the upper Yangtze River (UYR), China. First, the urban sprawl index (USI) is employed to assess the level of urban sprawl and to determine the characteristics of urban sprawl un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cities grow with the development of human society, and modern urban spaces are evolving towards the future. Every city in the world has formed its own urban spatial characteristics since their beginning, and different urban spaces have different characteristics [ 1 ]. The formation, development, and evolution of urban spaces have their own rules.…”
Section: Introductionmentioning
confidence: 99%
“…Cities grow with the development of human society, and modern urban spaces are evolving towards the future. Every city in the world has formed its own urban spatial characteristics since their beginning, and different urban spaces have different characteristics [ 1 ]. The formation, development, and evolution of urban spaces have their own rules.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the spatiotemporal evolution characteristics of CLE, some studies discussed the trend of CLE in the past decades [ 7 ], while others predicted the trend of CLE in the future [ 2 , 10 , 22 ]. The method, such as the sprawl intensity index [ 23 ], exponential landscape expansion index [ 24 , 25 ], spatial center shift model, urban land expansion estimation [ 26 ], and ArcGIS-based spatial analysis [ 27 ], have been mainly used in the analysis of a single city [ 18 ], urban agglomeration, or provincial area [ 27 , 28 , 29 ], all cities in a given nation [ 30 , 31 ] and global scale [ 10 , 26 ]. Concerning the driving factors of CLE, many scholars have proposed that CLE is affected by population growth [ 32 , 33 ], and economic development [ 34 , 35 , 36 ], while others have indicated that CLE is related to the behavior of local governments [ 23 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%